Directional strength and stiffness characteristics of inherently anisotropic sand: The influence of deposition inclination. Issue 137 (October 2020) - Zamanian, Mostafa; Mollaei-Alamouti, Vahid; Payan, Meghdad
Abstract: Evolution of soil fabric during deposition, sedimentation and subsequent shearing has been the focus of innumerous experimental and numerical studies in the past. However, the effect of inclined bedding plane on the mechanical behavior of granular materials has not been well recognized mostly due to the difficulties associated with the relevant simulations in the laboratory. In this study, a comprehensive experimental program is carried out to rigorously examine the significant influence of inclined bedding plane and deposition angle on the mechanical behavior of sands over a wide range of strains, from very small to large levels. To this end, specimens at different bedding plane angles are first prepared, frozen and then subjected to several consolidated drained (CD), consolidated undrained (CU) and bender element tests. Results show that the small strain shear stiffness and tangent axial stiffness are heavily influenced by the major principal stress direction and the deposition inclination. In terms of tangent axial stiffness, this effect is highlighted particularly before peak shear strength where the mechanical behavior of the granular material is dominated by particle interlocking. Besides, the anisotropic response of the soil is more pronounced at higher isotropic confining pressures. The volumetric behavior, internal friction angle and shear band direction are also observed to be remarkably dependent on the angle of bedding plane. Highlights: Influence of inclined bedding plane on the behaviour of sands was investigated. Large strain response of sand was evaluated at different bedding plane angles. Small strain shear stiffness decreased with the increase in the bedding plane angle. Anisotropic response of sand was more pronounced at higher confining pressures. Friction angle and shear band direction were dependent on deposition inclination.